The Potential of the Human Respiratory System e-Worksheet based on the Guided Inquiry in Empowering Critical Thinking Skills - Saputri, Wulandari; Nizkon, Nizkon; Agusta, Erie; Novyanti, Agustina (research, training and philanthropy institution Natural Aceh, 2023)
The presence of the covid pandemic, technological advances, and the complexities of the 21st century demand renewal of teaching materials in schools. Guided Inquiry learning models can also bridge the empowerment of critical thinking skills. This study aims to: 1) describe the feasibility of the e-worksheet based on expert judgment, 2) describe the practicality of the e-worksheet based on the teacher's assessment, and 3) describe the results of the e-worksheet readability assessment by students. This development research refers to the ADDIE development procedure. However, this research was only carried out up to the development stage due to limitations. The results of the feasibility assessment by material experts, teaching materials experts, and linguists showed that the e-worksheet was categorized as valid with a score of 80.00, 74.00, and 90.00, respectively. Then, the teacher's assessment results showed that the e-worksheet was in the practical category, scoring 92.00 and 94.00. Finally, the student readability test results showed that the e-worksheet could be read well, with scores of 93.61 and 93.88. Thus, the respiratory system e-worksheet based on the developed guided inquiry model can be recommended to improve students' critical thinking skills.